Analysis of broadband services diffusion in OECD 30 countries: Focusing on open access obligations - Sobee Shinohara; Yuji Akematsu; Masatsugu Tsuji (International Telecommunications Society (ITS), 2011)
Deployment of broadband for everyone has become a major policy objective in many countries, including Japan and the U.S. Recently, the U.S. announced a National Broadband Plan which is aimed at providing 100 million households with access to 100 Mbps broadband services by 2020. The purpose of this paper is to conduct an empirical analysis to identify factors affecting broadband service diffusion in OECD 30 member countries. First, considering the ratios by broadband technologies, we categorize major countries into CATV (BB) type, DSL type and FTTx type. Then, the paper postulates the following four hypotheses by an international comparison method: (1) initial conditions of Cable TV around year 2000 promote CATV (BB) diffusion; (2) open access obligations on copper subscriber lines affect DSL diffusion; and (3) relative connection speed of FTTx to DSL and (4) business strategy of operator for investment in FTTx influence FTTx diffusion. Finally, the paper empirically proves the above hypotheses by panel data model, which take care of the endogeneity problem using instrumental variable method. This analysis will provide an important basis for national broadband policy formulation in individual countries.
Keywords: 330; OECD; Broadband; FTTx; DSL; CATV (BB); open access obligations; unbundling; collocation; panel data analysis; instrumental variable method